Navigating Digital Era Challenges: Resilience AmongEducators in Sindh (Pakistan) (Journal of Asian Development Studies, 2024)
This research aimed at establishing the coping techniques that teachers in Sindh, Pakistan have adopted to deal with impacts of digital age. Qualitative case study research design was used in this study. Ten teachers from various teaching backgrounds in Sindh was selected to collect the data. The purposeful recruitment of these participants was with the intention of capturing possible diversity in the participant’s experiences and Precarious Academic Interests, such as teaching in rural and urban areas and in the public as well as the private schools as well as in terms of their readiness with digital learning resources. The results of the research show that educators’ resilience not only involves the technological perspective of how they accommodate themselves to learning, but also is a combination of cognitions and emotions, professionalism, collaboration, and individual flexibility. Teachers managed challenges of digital education on teaching by creating anticipatory measures and asking for help from other teachers as an illustration of strength of interpersonal connections. The work provides the educational leaders and policymakers with the insights of how to ensure the teacher flourishing and their professional development in the context of the continuous digitalization of education.